Group quenching and galactic conformity at low redshift. Issue 2 (22nd March 2018) - Treyer, M; Kraljic, K; Arnouts, S; de la Torre, S; Pichon, C; Dubois, Y; Vibert, D; Milliard, B; Laigle, C; Seibert, M; Brown, M J I; Grootes, M W; et al.
Abstract: We quantify the quenching impact of the group environment using the spectroscopic survey Galaxy and Mass Assembly to z  ∼ 0.2. The fraction of red (quiescent) galaxies, whether in groups or isolated, increases with both stellar mass and large-scale (5 Mpc) density. At fixed stellar mass, the red fraction is on average higher for satellites of red centrals than of blue (star-forming) centrals, a galactic conformity effect that increases with density. Most of the signal originates from groups that have the highest stellar mass, reside in the densest environments, and have massive, red only centrals. Assuming a colour-dependent halo-to-stellar-mass ratio, whereby red central galaxies inhabit significantly more massive haloes than blue ones of the same stellar mass, two regimes emerge more distinctly: at log ( M halo /M⊙ ) ≲ 13, central quenching is still ongoing, conformity is no longer existent, and satellites and group centrals exhibit the same quenching excess over field galaxies at all mass and density, in agreement with the concept of 'group quenching'; at log ( M h /M⊙ ) ≳ 13, a cut-off that sets apart massive (log ( M ⋆ /M⊙ ) > 11), fully quenched group centrals, conformity is meaningless, and satellites undergo significantly more quenching than their counterparts in smaller haloes. The latter effect strongly increases with density, giving rise to the density-dependent conformity signal when both regimes are mixed. The star formation of blue satellites in massive haloes is also suppressed compared to blue field galaxies, while blue group centrals and the majority of blue satellites, which reside in low-mass haloes, show no deviation from the colour–stellar mass relation of blue field galaxies.